The introduction of «The Passport of Health» in the educational process of the specialists of physical education. - Zakharina E.A. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2011)
The physical quality dates, physical health indices, the student's physical fitness were systematized. The data received were introduced in the developed "The Passport of Health", which was adapted to the educational process of the discipline "The rise of the sportsmanship of the selected sport". The analysis of data was proposed to the students, as well as filling passport during the whole education process.